(untitled) (Research, Society and Development, 2021)
Aim: To compare the Nursing Activities Score (NAS) scores obtained in 2015 and 2016 in a Neonatal ICU (NICU) after an educational intervention with nurses. Method: Retrospective, comparative, before-and-after study. Sample consisted of secondary data from NAS scores, from January 2015 to December 2016. Data analysis through descriptive statistics and t-Student test (P<0.05). Results: Mean annual scores revealed values of 70.5 (2015) and 78.8 (2016), evidencing that the hours of nursing care demanded by patients increased from 16.98 to 19.06 hours. In the post-intervention period, the average monthly NAS value was 84.6 (2016), while in the same period of the previous year it had been 69.3. The conversion of these values represents 16.63 hours (2015) and 20.03 hours (2016). Conclusion: The positive impact arising from the educational intervention is highlighted, ratifying the need for permanent education for health professionals.